PEDAGOGICAL PRINCIPLES OF PREPARING YOUNG SOCCER PLAYERS FOR COMPETITION THROUGH TECHNICAL AND TACTICAL SKILLS - Savar Bakhodirov Sirojiddinovich (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, the improvement of technical and tactical movements in football consists in developing the ability to control one’s movements with the active participation of the mind, the insufficient connection between the mind and the muscle-joint feeling prevents the achievement of the result, therefore, young football players are physically It is thought that education should be provided. Also, according to the hypothesis of creating a motor idea about technical equipment and its elements in the formation of motor skills in children, it is noted that by increasing the technical and tactical preparation of 13-14-year-old football players in the annual training cycle, the results of athletes’ performances in competitions will improve.